DESIGN AND LEGAL ASPECT OF CENTRAL BANK DIGITAL CURRENCY: A LITERATURE REVIEW - Handayani, Fitri; Yuliana, Fatma (Bank Indonesia, 2022)
The development of digitalisation in the financial services sector has compelled Bank Indonesia to develop Central Bank Digital Currency (CBDC). CBDC as a new type of money requires adjustments in terms of applicable laws and regulations. In an attempt to identify the design and legal regulations regarding CBDC, this paper performs a literature review through various related studies carried out internationally and in Indonesia. The novelty of this paper is to apply the rule of law to each selected CBDC design. Based on the study, CBDC design consists of wholesale and retail that can use token or account-based authentication. Then, CBDC transactions can be managed by the central bank or transacted through a Distributed Ledger Technology (DLT) system. In addition, another CBDC characteristic is based on interest-bearing and non-interest-bearing. The different implementation and selection of CBDC resulted in regulations that needed to be improved. Related to the legal aspect of CBDC in Indonesia, revisions are required to the substance of Law No. 7 of 2011 on Currency which must state that the form of rupiah includes CBDC. Furthermore, other rules that need to be considered are privacy and property laws, DLT, and insolvency law, as well as regulation of competition between CBDC and depository banks.